Metabolism of the radioprotective agent aminopropyl-methyl-isothiourea in mice - Xia Shou-xuan; Chen Neng-qian; Shen Bei-feng; Xu Hui-ying; Zhao Su-min; Shen Wen-mei (Acta Pharmacologica Sinica, 2016)
The absorption, distribution, excretion and biotransformation of 35S labeled (3-aminopropyl0-N’-methyl-isothiourea dihydrochloride(APMT) were studied in mice.1. The plasma concentrations of the drug after ip or po APMT were closely related to the radioprotective effects.2. APMT was almost unabsorbed in stomach,but was quickly and completely absorbed in small intestine. The excretion was rapid;most of it was excreted from urine within 24 h. The total radioactivity was almost entirely recovered from the excreta after 72 h. 3. The radioactivity was much higher in bone marrow and spleen than in plasma. The effectiveness of the drug was proportional to the radioactivities distrituted in these tissues. The metabolites in these tissues were analyzed by paper chromatography and subsequent scanning. 4. The distribution of the drug in the cell nuclei, mitochondria and 9000 g supernatants of spleen and liver cells were determined by differential centrifugation. The radioactivity was higer in the nuclei fraction and more firmly bound with mitochondria in the spleen cells than that in the liver cells. Its significance was discussed in connection with the protective action of the drug on hematopoietic tissue.